2010
DOI: 10.1016/j.marenvres.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of Atlantic cod (Gadus morhua) exposed to produced water during early life stages: Effects on embryos, larvae, and juvenile fish

Abstract: Produced water (PW) contains numerous toxic compounds of natural origin, such as dispersed oil, metals, alkylphenols (APs), and polycyclic aromatic hydrocarbons (PAHs). In addition, PW also contains many different chemicals which have been added during the oil production process. In the study described here, cod were exposed to real PW collected from an oil production platform in the North Sea. This was done in order to best recreate the most realistic field-exposure regime in which fish will be affected by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 90 publications
3
24
0
1
Order By: Relevance
“…As a result, measured PAH concentrations in that stock solution as well as in the various experimental dilutions were in line with reported values in similar experiments (Aas et al 2000;Meier et al 2010;Milinkovitch et al 2011Milinkovitch et al , 2012Sundt et al 2012). As a result, measured PAH concentrations in that stock solution as well as in the various experimental dilutions were in line with reported values in similar experiments (Aas et al 2000;Meier et al 2010;Milinkovitch et al 2011Milinkovitch et al , 2012Sundt et al 2012).…”
Section: Discussionsupporting
confidence: 89%
“…As a result, measured PAH concentrations in that stock solution as well as in the various experimental dilutions were in line with reported values in similar experiments (Aas et al 2000;Meier et al 2010;Milinkovitch et al 2011Milinkovitch et al , 2012Sundt et al 2012). As a result, measured PAH concentrations in that stock solution as well as in the various experimental dilutions were in line with reported values in similar experiments (Aas et al 2000;Meier et al 2010;Milinkovitch et al 2011Milinkovitch et al , 2012Sundt et al 2012).…”
Section: Discussionsupporting
confidence: 89%
“…cod (Gadus morhua) embryos and larvae exposed to produced oil discharge water and E2 exhibit higher mortality and impacts to fitness than in fish exposed as post-metamorphic juveniles (Meier et al, 2010). Similar life stage-dependent effects have been demonstrated in zebrafish (Brion et al, 2004), medaka (Koger et al, 2000), and fathead minnow (van Aerle et al, 2002).…”
Section: Introductionmentioning
confidence: 75%
“…No significant differences in morphometric parameters between exposed and control organisms were found, indicating that growth rate was not affected by electric field exposure. Furthermore, exposed and control groups did not exhibit differences in the occurrence of morphometric changes, such as jaw deformities (which are known to prevent feeding; Tilseth et al 1984;Meier et al 2010), abnormal yolk resorption, increased incurvation, or deformations (e.g., lordosis and scoliosis).…”
Section: Discussionmentioning
confidence: 95%
“…In general, this developmental stage is known to be a bottleneck period in Atlantic Cod larviculture conditions, as failure to initiate and maintain sufficient feeding is the major factor contributing to mass mortality Brown 1999, 2002;Brown et al 2003). In contrast, Atlantic Cod at later developmental stages (i.e., larvae in metamorphosis and juveniles) display higher survival rates and appear to be more robust (Pedersen and Falk-Petersen 1992;Opstad et al 2006;Meier et al 2010). Indeed, in the present study, no differences in survival were found for Atlantic Cod exposed during metamorphosis (46 DPH) or at the juvenile stage (60 DPH).…”
Section: Discussionmentioning
confidence: 99%